Peripherally derived angiotensin converting enzyme-enhanced macrophages alleviate Alzheimer-related disease - Koronyo-Hamaoui, Maya (Brain, 2020)
Targeted overexpression of angiotensin-converting enzyme (ACE), an amyloid-β protein degrading enzyme, to brain resident microglia and peripheral myelomonocytes (ACE(10) model) substantially diminished Alzheimer’s-like disease in double-transgenic APP(SWE)/PS1(ΔE9) (AD(+)) mice. In this study, we explored the impact of selective and transient angiotensin-converting enzyme overexpression on macrophage behaviour and the relative contribution of bone marrow-derived ACE(10) macrophages, but not microglia, in attenuating disease progression. To this end, two in vivo approaches were applied in AD(+) mice: (i) ACE(10/GFP+) bone marrow transplantation with head shielding; and (ii) adoptive transfer of CD115(+)-ACE(10/GFP+) monocytes to the peripheral blood. Extensive in vitro studies were further undertaken to establish the unique ACE(10)-macrophage phenotype(s) in response to amyloid-β(1-42) fibrils and oligomers. The combined in vivo approaches showed that increased cerebral infiltration of ACE(10) as compared to wild-type monocytes (∼3-fold increase; P < 0.05) led to reductions in cerebral soluble amyloid-β(1-42), vascular and parenchymal amyloid-β deposits, and astrocytosis (31%, 47–80%, and 33%, respectively; P < 0.05–0.0001). ACE(10) macrophages surrounded brain and retinal amyloid-β plaques and expressed 3.2-fold higher insulin-like growth factor-1 (P < 0.01) and ∼60% lower tumour necrosis factor-α (P < 0.05). Importantly, blood enrichment with CD115(+)-ACE(10) monocytes in symptomatic AD(+) mice resulted in pronounced synaptic and cognitive preservation (P < 0.05–0.001). In vitro analysis of macrophage response to well-defined amyloid-β(1-42) conformers (fibrils, prion rod-like structures, and stabilized soluble oligomers) revealed extensive resistance to amyloid-β(1-42) species by ACE(10) macrophages. They exhibited 2–5-fold increased surface binding to amyloid-β conformers as well as substantially more effective amyloid-β(1-42) uptake, at least 8-fold higher than those of wild-type macrophages (P < 0.0001), which were associated with enhanced expression of surface scavenger receptors (i.e. CD36, scavenger receptor class A member 1, triggering receptor expressed on myeloid cells 2, CD163; P < 0.05–0.0001), endosomal processing (P < 0.05–0.0001), and ∼80% increased extracellular degradation of amyloid-β(1-42) (P < 0.001). Beneficial ACE(10) phenotype was reversed by the angiotensin-converting enzyme inhibitor (lisinopril) and thus was dependent on angiotensin-converting enzyme catalytic activity. Further, ACE(10) macrophages presented distinct anti-inflammatory (low inducible nitric oxide synthase and lower tumour necrosis factor-α), pro-healing immune profiles (high insulin-like growth factor-1, elongated cell morphology), even following exposure to Alzheimer’s-related amyloid-β(1-42) oligomers. Overall, we provide the first evidence for therapeutic roles of angiotensin-converting enzyme-overexpressing macrophages in preserving synapses and cognition, attenuating neuropathology and neuroinflammation, and enhancing resistance to defined pathognomonic amyloid-β forms.